The influence of cannabis on sexual functioning and satisfaction - Amanda Moser; Sharon M. Ballard; Jake Jensen; Paige Averett (Journal of Cannabis Research, 2023)
Abstract Background The purpose of this study was to examine the perceived influence of cannabis on sexual functioning and satisfaction. This study used Kaplan’s and Masters and Johnson’s sexual response cycle (desire, excitement, orgasm, plateau, resolution) and included satisfaction to complete the sexual response cycle. Given increased attention in the research literature to the potential benefits of cannabis and the lack of research on the sexual benefits of cannabis use, the current study was completed. Methods Data were collected using the online survey tool “Qualtrics” from a self-selected, convenience sample of adults over the age of 18 who reported previous cannabis use. The survey, developed by the researchers based on previous literature, included demographic questions followed by a scale to measure sexual functioning and satisfaction in relation to cannabis use (α = 0.897). Results The final sample was 811 participants ranging in age from 18 to 85 years old (M = 32.11). The majority of participants were identified as female (n = 536, 64.9%), White/Caucasian (n = 640, 78.9%), and college educated (n = 650, 80.1%). Almost 25% of the participants were identified as LGBTQIA+ (n = 187, 23.1%). Most of the participants reported being in a monogamous sexual relationship (n = 598, 73.7%). Data were analyzed using descriptive statistics, t-tests, one-way ANOVA, and multiple regression. Age and gender were not found to have significant effects on cannabis use and sexual functioning and satisfaction. Over 70% of participants reported increased desire (M = 4.05, SD = 0.962) and orgasm intensity (M = 4.05, SD = 0.884). Participants who reported masturbating indicated that cannabis enhanced their pleasure while masturbating (n = 620, 62.5%). Participants also stated that cannabis enhanced their sense of taste (n = 583, 71.9%) and touch (n = 576, 71.0%). Discussion The results of this study contrast and establish new evidence within the literature. Demographic results indicate that the people who use cannabis are of a wide range of ages, from a variety of occupations, and have differing cannabis use preferences. The inclusion of LGBTQIA + respondents is a strength of this study. Overall, results indicated that both men and women perceived that cannabis use increased their sexual functioning and satisfaction, particularly increased desire and orgasm intensity. Conclusion This study updates the current literature on cannabis and sexuality and provides implications for improving sexual quality. Medical implications of this study include the possible use of cannabis for treating sexual dysfunctions, especially within women.